Stereoselective Total Synthesis of Macrolide Sch-725674 and C-7-epi-Sch-725674 - Baikadi, Karunakar; Talakokkula, Anil; Narsaiah, A. Venkat (SynOpen, 2019)
The stereoselective total synthesis of Sch-725674 in 14 linear synthetic steps with 10.3% overall yield is described. The synthesis started from commercially available starting materials, d-ribose and (R)-benzyl glycidol. The key reactions involved CBS reduction, Julia–Kocienski olefination, Horner–Wadsworth–Emmons reaction, and Shiina macrolactonization.
Keywords: natural product synthesis; macrolides; Sch-725674; C-7-epi-Sch-725674; antifungal agents